ФОРМУВАННЯ ОРГАНІЗОВАНОСТІ УЧНІВ У ПРОЦЕСІ ЇХНЬОЇ НАВЧАЛЬНО-ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2003)
Formation of Pupils’ Organization in the Process of their Science Researching Activity. The definition of the conception of the organization in science - researching activity is given. Its relations with the conceptions of self-organization; scientific approach to work and culture of mental activity aresubstantiated Inseparable ties of organization and science-researching activity are founded, it is also proved that the methods and means of formation of the quality mentioned depend on the type of academic activity. The peculiarities of science-researching activity of the senior pupils are. found out, the criteria of the definitions of the level of organization in different types of science-researching activity are developed. The definitions of criteria are based on the cognitive and regulating components of the position of the subject of learning.